The Influence of Shopping Lifestyle and Fashion Involvement on Impulse Buying Behavior of Uniqlo Product at Shopee - Natacsya L. B. Mawara; Frederik G. Worang; Ferdinand J. Tumewu (Universitas Sam Ratulangi, 2022)
There are many factors that trigger impulse buying, some of which are shopping environment factors, in-store promotion factors, and service quality factors. The purpose of this study is to see the influence of shopping lifestyle and fashion involvement on impulse buying behavior of Uniqlo products at shopee, this study is a quantitative study and uses a multiple linear regression method. The findings of this study shows that the independent variables which are shopping lifestyle and fashion involvement influence the impulse buying behavior, in this case of Uniqlo product at Shopee. Based on the result, the researcher provided several recommendations which are for the application to do prority setting in term of shopping preferences, by doing so it will create a better prospect especially in term of reducing the sense of hedonistic traits. Also adding direct sense of involvement into other activities, meaning that it will reduce the involvement regarding the fashion sense.